Republic of Korea : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Korea. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation discusses Korea's economy that has strong fundamentals; however, it is facing cyclical and structural headwinds. Potential growth will continue its decline, and polarization and inequality are concerns. Labor and product market duality persist. The government is focusing on supporting income, creating jobs, and promoting innovation. The government has focused on supporting income, creating jobs, and promoting innovation. It has strengthened social safety nets, substantially raised the minimum wage, supported small-and-medium enterprises to boost employment, and expanded public sector jobs. Fiscal policy should remain expansionary in the medium term, focusing on increasing social protection, boosting female labor force participation, and supporting growth enhancing structural reforms. Public sector job creation should be linked to developing services that cannot be provided by the private sector. The minimum wage increase for next year should be set below labor productivity growth. The IMF staff recommend an integrated package of macroeconomic, financial and structural policies to support growth, raise potential output, and reduce excess internal and external imbalances, while preserving financial stability.